Implementation of Literacy Culture to Increase Students' Interest in Reading At MI Infarul Ghoy (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2025)
Students' current interest in reading shows a decline, which is influenced by several factors. Education problems in Indonesia still focus on the low level of student literacy. This is largely due to a lack of interest in reading, which is influenced by technological advances and a lack of motivational support from parents and teachers. In fact, reading activities can open up new knowledge, help find information, and expand horizons. This study aims to: (1) assess students' reading interest in MI Infarul Ghoy, (2) evaluate the application of literacy culture in MI Infarul Ghoy, and (3) examine the relationship between students' reading interest and the application of literacy culture at MI Infarul Ghoy. This research uses a qualitative approach. The results of the study at MI Infarul Ghoy showed that students' reading interest was classified in the